2010
DOI: 10.1542/peds.2010-0941
|View full text |Cite
|
Sign up to set email alerts
|

Association BetweenHelicobacter pyloriand Gastrointestinal Symptoms in Children

Abstract: We found no association between RAP and H pylori infection in children and conflicting evidence for an association between epigastric pain and H pylori infection. We found evidence for an association between UAP but could not confirm this finding in children seen in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
3
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 43 publications
1
63
3
10
Order By: Relevance
“…26 There was no statistical significant difference in the incidence of H. pylori infection between the symptomatic and asymptomatic group of children (42.65 and 45%, p>0.05) indicating existence of no relation between RAP and H. pylori infection. 11,[26][27][28] However, the association of recurrent abdominal pain (RAP) and H. pylori is still debatable and other studies have reported an association between the two. 29,30 On the other hand, there is evidence against this association.…”
Section: It Is Not Yet Clear Whether the Difference In Anthropometry mentioning
confidence: 99%
See 2 more Smart Citations
“…26 There was no statistical significant difference in the incidence of H. pylori infection between the symptomatic and asymptomatic group of children (42.65 and 45%, p>0.05) indicating existence of no relation between RAP and H. pylori infection. 11,[26][27][28] However, the association of recurrent abdominal pain (RAP) and H. pylori is still debatable and other studies have reported an association between the two. 29,30 On the other hand, there is evidence against this association.…”
Section: It Is Not Yet Clear Whether the Difference In Anthropometry mentioning
confidence: 99%
“…10 These first recommendations were based on the lack of proof that infection with HP is a significant cause of GI symptoms. 11 Symptoms suggestive of acute HP infection are similar to several common childhood disorders, manifesting as recurrent abdominal pain, dyspepsia, epigastric pain, diarrhea and vomiting. 12 For the diagnosis of HP infection, gastrointestinal endoscopy with tissue culture is considered to be the "gold standard".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between recurrent abdominal pain and H. pylori infection is controversial. Some studies show that H. pylori is more frequent in patients with RAP compared to asymptomatic children, while others do not find an association between RAP and H. pylori infection [23][24][25][26][27][28][29][30]. H. pylori infection has also been reported with nonspecific symptoms, such as epigastric pain, dyspepsia, halitosis, nausea, vomiting and retrosternal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Birçok çalışmada H. pylori ile TKA arasında ilişki bulunmamış ve TKA olan ço-cuklarda H. pylori taramasının gerekli olmadığı belirtilmiştir. [15][16][17][18][19][20] Kronik gastrik inflamasyonun sitokin salınımı aracılığı ile viseral hiperaljeziye yol açtığı ve H. pylori'nin rektoviseral gastrokolonik refleksin tetiklenmesinde rol alabileceği düşünül-mektedir. 8 Ülkemizde sağlıklı çocuklarda H. pylori sıklığı 13 C-üre nefes testi ile %50-56 olarak bulunmuştur, TKA'sı olan çocukların %36-49'unda ise H. pylori organik neden olarak bildirilmiştir.…”
Section: Bulgularunclassified